Voter Behavior in Regional Head Elections During the Covid-19 Pandemic: Data and Analysis - Mohammad Hidayaturrahman; Enza Resdiana; Ahmad Hasan Ubaid; Elazhari Elazhari (Jurnal Politik Indonesia: Indonesian Political Science Review, 2023)
This research was conducted to analyze how voters behave in regional head elections in Indonesia, during the Covid-19 pandemic. The method used in this research is descriptive qualitative. Data collection was carried out by means of in-depth interviews with various informants who were directly involved in the election of regional heads, election committees, election supervisors and voters. In addition, data collection was also carried out by tracing documents relevant to the research topic, both documents originating from the election committee and supervisors. From the research that has been done, it has been revealed that the voters in the regional head election which took place in Sumenep Regency, Indonesia in 2020 behaved pragmatically and permissively towards money politics. This was caused by the poor economic conditions of voters, during the Covid-19 pandemic. This pragmatic behavior also encourages their presence to choose a pair of candidates who give money. Thus, the level of voter turnout and participation in regional head elections is higher than before the Covid-19 pandemic. This research has limitations in the scope of research, which is only carried out in Sumenep Regency, Indonesia in 2020, so it cannot represent Indonesian society in general.